Optimization of ultrasonic assisted ethanolic extraction for natural pigments from butterfly pea flower applied in Thai dessert using Box-Behnken approach - Samart Sai-Ut; Apisara Teksee; Jaksuma Pongsetkul; Sirima Sinthusamran; Saroat Rawdkuen (My University, 2024)
Butterfly pea is a natural color source used in food and dessert. This study optimized ultrasound-assisted extraction with ethanol for pigments from butterfly pea flowers (BPF) using a Box-Behnken method. Key factors explored were solid-to-solvent ratio, ultrasound extraction time, and ethanol concentration. The extracted compounds were evaluated for extraction yield (EY), total phenolic content (TPC), total anthocyanin content (TAC), and DPPH antioxidant activity. EY increased significantly with reduced ethanol concentration. Optimal conditions were predicted and experimentally validated. BPF extracts showed distinct absorption wavelengths at different pH levels. BPF extract was used in coconut milk jelly, resulting in the lowest
Keywords: BoxBehnken design; Natural dye; Phytochemicals and Antioxidant Activities